RAVEN: Optimizing Power Consumption of Mobile Games Using Perception-Aware Rendering Rate Scaling - Liu, Yunxin (accepted to appear in the 23rd Annual International Conference on Mobile Computing and Networking (MobiCom 2017), 2017)
ACM MobiCom 2017, the Annual International Conference on Mobile Computing and Networking, is the twenty third in a series of annual conferences sponsored by ACM SIGMOBILE dedicated to addressing the challenges in the areas of mobile computing and wireless and mobile networking. The MobiCom conference series serves as a highly selective, premier international forum addressing networks, systems, algorithms, and applications that support mobile computers and wireless networks. In addition to the regular conference program, MobiCom 2017 will include a set of workshops, panels, research demonstrations, and a poster session that includes the ACM Student Research Competition. MobiCom will again feature the mobile app competition successfully introduced three years ago. The conference will be held at the SnowBird resort close to Salt Lake City, Utah, USA.